A Nexus of Sensationalism and Politics: Doar Ha-Yom and the 1929 Western Wall Crisis. Issue 2 (1st September 2019) - Elyada, Ouzi
Abstract : This article looks at how a group of radical Revisionist journalists who assumed effective control of the newspaper Doar Ha-Yom in July 1929 attempted to fuse politics and sensationalism against the background of the Western Wall affair that, in late August of that year, evolved into the violent incidents collectively known as the 1929 riots (or massacres). Examination of the paper during the month preceding the riots shows clearly that its editors made a systematic attempt to inflame the Jewish population of Mandate Palestine. These sensationalist editing techniques, reminiscent of the pamphleteer style, were employed not only to sell more copies of the paper, as had been the case before the Revisionists took control, but also to advance Revisionist political goals. The article examines the model that the Revisionists used to shape their incendiary strategy, the provocative process itself, and the question of the editors' responsibility for the 1929 riots.